Survey Paper for Dynamic Resource Allocation using Migration in Cloud (International Journal of Engineering and Computer Science, 2014)
Cloud Computing is a rampant technology nowadays because of its scalability, flexibility, availability of resources and the other features. In cloud computing resource multiplexing is done through the virtualization technology. Virtualization technology is acts as a backbone for provisioning requirements of a cloud based solution. The problems arising in cloud computing using virtualization must be solved. In present cloud computing environment, load balancing is one of the challenging issues. To present a better approach for solving the problem of VM resource scheduling in a cloud computing environment, uses CPU and network usage calculation. A load predictor is used to predict the load in future, according to the this , it allocate the resources. For multiplexing of virtual machines to physical machines is managed using the Usher framework. Introducing the skewness algorithm to measure the resource utilization of server and minimizing the skewness can improve overall utilization of server and for load balancing the migration technology is used. Using this migration, can achieve the green computing.